Functional Impairment of Circulating FcεRI+ Monocytes and Myeloid Dendritic Cells in Hepatocellular Carcinoma and Cholangiocarcinoma Patients. Issue 6 (4th March 2019) - Martín‐Sierra, Carmen; Martins, Ricardo; Laranjeira, Paula; Abrantes, A. Margarida; Oliveira, R. Caetano; Tralhão, J. Guilherme; Botelho, M. Filomena; Furtado, Emanuel; Domingues, Rosário; Paiva, Artur
Abstract : Background: Hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA) represent the most common primary liver malignancies whose outcome is influenced by the immune response. Methods: In this study, we have functionally characterized, by flow cytometry, circulating myeloid dendritic cells (mDCs) and FcεRI + monocytes in a group of healthy individuals ( n = 10) and in a group of patients with HCC ( n = 19) and CCA ( n = 8), at the time point of the surgical resection (T0) and once the patient had recovered from surgery (T1). Moreover, we proceeded to a more in depth phenotypic characterization of the FcεRI + monocyte subpopulation. Results: A significant decrease in the frequency of TNFα producing FcεRI + monocytes and mDCs in HCC and CCA patients when compared to the group of healthy individuals was observed, and a close association between FcεRI + monocytes and mDCs dysfunction was identified. In addition, the phenotypic characteristics of FcεRI + monocytes from healthy individuals strongly suggest that this population drives to mDCs, which matches with the fact that both populations are functionally affected. Conclusions: The frequency and the function of circulating mDCs and FcεRI + monocytes are affected in both HCC and CCA patients, and FcεRI + monocytes could represent those fated to become mDCs. © 2019 International Clinical Cytometry Society